Incidence of the application of the multiple intelligences teaching strategies In the level of development of English language skills with students of the 6th and 7th grades at the MIGUEL DE UNAMUNO Private Bilingual Institute, School Year 2006 - 2007 - Almeida García, Evelyn Verónica (2007)
Miguel de Unamuno is a Private Bilingual Institute which offers elementary education from kinder Garden until tenth grade. It is located on 1838 Sozoranga St. and Serapio Japeravi Ave, in Union y Justicia Community in Quito. The owner and Principal is Mrs. Asalia Báez de Morales. The Bilingual Institute MIGUEL DE UNAMUNO has difficulty in implementing new teaching techniques because of the teaching process which was based on a traditional view. It is important that new and updated techniques would influence on the students learning of the language more effectively. The thesis is structured with the following chapters: Chapter I is about the Problem Identification of the Institute, the Variables, Objective and Justification of the Thesis. Chapter II refers to Theoretical Frame, the different Teaching Methods for learning the language, Models of Motivation and specially talks about the Multiple Intelligence Theory. Chapter III talks about Methodological Design of the Investigation, the Process and Analysis of Data which lead us to conclusions that the teaching strategies based on the multiple intelligences theory have a favorable incidence in the level of development of English Language Skills with students of the 6th and 7th years at the Miguel de Unamuno Institute and that the institute does apply the correct teaching techniques to interest the students in the learning of the foreign language. Therefore; the final Chapter IV refers to the proposal about the increment of a Teaching Training Program Based on The Multiple Intelligences Theory for the institution.